Comparative analysis of different methods for evaluating quality of Quercus ilex seedlings inoculated with Tuber melanosporum - Andres-Alpuente, Antonio; Sanchez, Sergio; Martin, Maria; Javier Aguirre, Angel; Barriuso, Juan J. (MYCORRHIZA, 2014)
The quality of seedlings colonized by Tuber melanosporum is one of the main factors that contributes to the success or failure of a truffle crop. Truffle cultivation has quickly grown in European countries and elsewhere, so a commonly shared seedling evaluation method is needed. Five evaluation methods are currently published in the literature: three are used in Spain and two in France and Italy. Although all estimate the percentage colonization by T. melanosporum mycorrhizae, they do it in different ways. Two methods also estimate total number of mycorrhizae per seedling. Most are destructive. In this work, ten batches of holm oak seedlings inoculated with T. melanosporum from two different nurseries were evaluated by means of the five methods noted above. Some similarity was detected between the percentages of T. melanosporum mycorrhizae estimated by each method but not in their ability to assess the suitability of each batch. We discuss the advantages and disadvantages for each method and suggest approaches to reach consensus within the truffle culture industry for certifying mycorrhizal colonization by T. melanosporum and seedling quality.
The following values have no corresponding Zotero field: pub-location: 233 SPRING ST, NEW YORK, NY 10013 USA publisher: SPRINGER
Keywords: Black truffle; Certification; Holm oak; Mycorrhization; Nurseries; Truffle culture

Persistence and detection of black truffle ectomycorrhizas in plantations: comparison between two field detection methods - Sanchez, Sergio; Agreda, Teresa; Agueda, Beatriz; Martin, Maria; de Miguel, Ana María; Barriuso, Juan; Sanchez, Sergio; Agreda, Teresa; Agueda, Beatriz; Martin, Maria; de Miguel, Ana María; Barriuso, Juan (MYCORRHIZA, 2014)
Owners of black truffle (Tuber melanosporum) plantations are concerned about the persistence of its mycorrhizas and mycelium in the soil, especially until the appearance of the ``truffle burn{''} areas and the triggering of sporocarp production, at least 5-7 years after planting truffle-inoculated seedlings. During this period, the farmer does not know whether his management is promoting black truffle development. To study the presence and abundance of T. melanosporum ectomycorrhizas in plantations, two sampling methods, direct sampling of root tips and soil core collection, are compared by analyzing 48 evergreen oak trees (Quercus ilex) inoculated with truffle. Those trees are grouped by age (< 6, 6-9, > 9 years old) and presence or absence of truffle production. T. melanosporum was present in 46 out of the 48 studied trees, and its ectomycorrhizas appeared in 65 % of the ectomycorrhizal tips. Its abundance is significantly higher with productive trees and young trees. Direct sampling of root tips and soil core collection were equally effective in detecting this species, although soil core collection proved a better method to also evaluate ectomycorrhizal fungal diversity. To detect the presence of T. melanosporum in a given plantation, three samples suffice, with a single sample per random tree. Although the presence of mycorrhizas is not a sure sign of the future success of a black truffle plantation, its absence influences managers as to whether to continue culturing truffles in a plantation.
Keywords: direct; Direct method; method; Mycorrhizas; Soil core method; Trufficulture; Tuber melanosporum